PENGARUH SIZE, LEVERAGE, PROFITABILITY, DAN AGE TERHADAP INTELLECTUAL CAPITAL DISCLOSURE (STUDI PADA PERUSAHAAN SEKTOR CONSUMER GOODS INDUSTRY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016) - NOVITA ANDRIYANA; Triana Fitriastuti; Djoko Setyadi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
This research was conducted to examine the effect of variable size, leverage, profitability, and age on intellectual capital disclosure. The research population includes all consumer goods industry sector companies listed on the Indonesia Stock Exchange for the 2012-2016 period. Samples were taken using purposive sampling method. Based on the predetermined criteria, there are 24 companies. The data used is secondary data. The data analysis method used is descriptive statistics. The results showed that size, leverage, and age did not affect intellectual capital disclosure. While profitability has an effect on intellectual capital disclosure.